Los derechos humanos: un principio rector de la responsabilidad social empresarial - Naydu Judith Jácome-Castilla; Magda Mildreth Rodríguez-Castilla; Marta Milena Peñaranda-Peñaranda (Mundo Fesc)
Currently, the term "Social Responsibility" has become strongly associated with corporate image, becoming a key factor in reflecting an organization's commitment to its stakeholders, as well as in implementing actions that promote the achievement of the Sustainable Development Goals. From this perspective, aspects such as the environment, good treatment of internal and external clients, community engagement in corporate policies, the protection of human rights, and long-term sustainability allow organizations to carry out their activities, seeking not only profit and economic growth, but also directly impacting quality of life, sustainability, respect, and equity. Viewed from the perspective of business management and humanistics, CSR assesses the level of organizational development in relation to respect for and promotion of stakeholder rights. Therefore, based on these postulates, we proceeded to characterize the socially responsible practices related to the human rights dimension carried out by 117 MSMEs dedicated to providing services in the city of Ocaña, Norte de Santander. Based on a quantitative, non-experimental, cross-sectional research, results were obtained that demonstrate how respect for human rights, equality, and social equity are important aspects for employers in the sector, despite the fact that most of them do not have a methodology and/or human resource recruitment strategies that contribute to diversity within their companies.